Поліцейські послуги в законодавстві України та на практиці - Зозуля, І. В.; Zozulia, I. V.; Зозуля Ігор (Форум права. – 2019. – № 3. – С. 21-38, 2019)
Узагальнено законодавчий, науковий та практичний досвід з проголошеної публічно-сервісної діяльності Національної поліції України щодо надання нею поліцейських послуг. Визначено поняття послуги та її особливостей, переходу до "сервісної" поліції та правових засад надання "сервісних" платних послуг в системі МВС України, новелізації поліцейських послуг у законодавстві України, розбіжностей подання сутності поліцейської послуги при проведенні тендерних процедур та сприйняття поліцейських послуг в наукових дослідженнях і закордонний досвід для України. Встановлено, що вітчизняно-орієнтований підхід до трактування поліцейської послуги сьогодні полягає в її основі одночасно як відокремленої від поліцейської діяльності її частини, так і функціональної наддіяльності, розповсюджуваної на усю сферу поліцейської діяльності. Висловлена дискусійна авторська пропозиція щодо можливості вилучення із Закону України "Про Національну поліцію" та суміжного законодавства терміну "поліцейські послуги", обмежившись загальною вказівкою, що Національна поліція в своїй діяльності надає, в межах законодавства, в тому числі і сервісні послуги, зміст, перелік та порядок надання яких визначено законом.

Problem statement. In the last four years, the legal and regulatory conflict has continued in Ukraine due to the inconsistency of scientific and legislative approaches to understanding the essence of police services. This indirectly affects both the activities of the National Police and the public's attitude to its activities. This state of affairs is unacceptable given the existence in the world of a legally established mechanism for understanding the essence of police services and providing them in practice, which Ukraine still rules by model. The purpose of the article is to summarize the legislative, scientific and practical experience of the proclaimed public-service activities of the National Police of Ukraine in the provision of police services. Methods. The research method is General scientific dialectical, formal-legal, comparative methods. Results. The author's position on the mechanism of understanding the essence of police services in the activities of the National Police of Ukraine and their provision in practice was expressed. The concept of service and its features are defined. The general transition to "service" police and legal bases of rendering "service" paid services in the system of the Ministry of Internal Affairs of Ukraine is considered. The peculiarities of the police services modernization in the legislation of Ukraine are defined. Discrepancies of representation of the essence of police service in carrying out of tender procedures are defined. Features of perception of police services in scientific researches and foreign experience in Ukraine are presented. Conclusions. It is established that the domestic-oriented approach to the interpretation of police service today is at the basis of both separated from police activity on its part and functional over-activity, which extends to the entire sphere of police activity. Discussion on the possibility of exclusion from the Law of Ukraine "On National Police" and related legislation of the term "police services", limited to, the general statement that the National Police in its activity providers, within the law, including services, content, list and the procedure for granting which is prescribed by law.

Обобщен законодательный, научный и практический опыт по провозглашенной публично-сервисной деятельности Национальной полиции Украины о предоставлении ею полицейских услуг. Определено понятие услуги и ее особенностей, перехода к "сервисной" полиции и правовых основ предоставления "сервисных" платных услуг в системе МВД Украины, новелизации полицейских услуг в законодательстве Украины, разногласий представлений сущности полицейской услуги при проведении тендерных процедур и восприятия полицейских услуг в научных исследованиях и зарубежный опыт для Украины.
Police services in Ukraine legislation and in practice
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; полиция; police; поліцейські послуги; сервісні послуги; полицейские услуги; сервисные услуги; police services; services